2016
DOI: 10.1212/wnl.0000000000003127
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics and prebiotic fiber for constipation associated with Parkinson disease

Abstract: This study provides Class I evidence that for patients with PD who have constipation, fermented milk containing probiotics and prebiotics increases the frequency of CBMs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
214
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 305 publications
(228 citation statements)
references
References 29 publications
6
214
0
8
Order By: Relevance
“…As highlighted by Knudsen and colleagues, a major shortcoming of the use of Rome III criteria in PD is the lack of studies . However, using these criteria, our research group published 4 studies (2 after February 2016), including a randomized trial on the use of prebiotics and probiotics as adjuvant therapy for constipation . In the first 3 studies, we found a prevalence of constipation ranging between 47% to 60% (pooled prevalence, 51%), which is consistent with the pooled estimates provided by the Danish colleagues.…”
supporting
confidence: 86%
See 2 more Smart Citations
“…As highlighted by Knudsen and colleagues, a major shortcoming of the use of Rome III criteria in PD is the lack of studies . However, using these criteria, our research group published 4 studies (2 after February 2016), including a randomized trial on the use of prebiotics and probiotics as adjuvant therapy for constipation . In the first 3 studies, we found a prevalence of constipation ranging between 47% to 60% (pooled prevalence, 51%), which is consistent with the pooled estimates provided by the Danish colleagues.…”
supporting
confidence: 86%
“…Finally, in our randomized clinical trial, we also provided—for the first time in a PD patient population—an indirect validation of this tool and a focus on the reliability of subjectively reported constipation. In particular, we observed that 120 out of 165 patients (73%) initially self‐reporting constipation had the diagnosis confirmed on the basis of the stool diary completed during the 2‐week pretreatment phase . Therefore, among PD patients, not only the prevalence of objective colonic dysfunction exceeds the prevalence of subjective constipation but also an overreporting of the symptom does exist.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Probiotics and prebiotic fiber were evaluated in 1 high‐quality, positive study . The new conclusions are “ efficacious ” and “ clinically useful .” There are no safety concerns, and given their wide availability and over‐the‐counter use in many countries, probiotics and prebiotic fiber are considered to pose an “ acceptable risk without specialized monitoring .”…”
Section: Results and Conclusionmentioning
confidence: 99%
“…A total of 3 new studies 12,39,40 were included for the treatment of gastrointestinal dysfunction in PD, and trials not fulfilling the inclusion criteria for review were excluded. 53,56,105 See Table 8 for recommendations.…”
Section: New Conclusionmentioning
confidence: 99%